Giant Blue Nevus: A New Association to Nevus of Ota. (August 2015) - Medel, Ramón; Vasquez, LuzMaria; Fernandez, Javier; Huguet, Pere; Pamias, Jordi
Abstract Nevus of Ota, also known as oculodermal melanocytosis, is a congenital pigmentary condition that can affect structures in the distribution of the ophthalmic and maxillary divisions of the trigeminal cranial nerve. Malignant transformation, although rare, may occur within nevus of Ota and result in uveal, cutaneous, orbital or even dural melanoma. We present a new association of Nevus of Ota complicated with a giant orbital Blue Nevus in a young white male and the management of this tumor.